The functions and responsibilities of a project management office to support university research centers - Fernandes, Aldora Gabriela Gomes (2019)
This paper describes a quantitative study to identify the functions and responsibilities (F&R) that a project management office should have to support university research centers, that organize their work by projects. The research study takes an evolutionary perspective, suggesting three different typologies of project management offices: basic, intermediate and advanced. An ‘initial conceptualization’ of the F&R for each one of the three project management office typologies, based on literature review, was tested through a survey, which elicited 242 valid responses from researchers involved in projects at university research centers. The paper focuses on factor analysis of the survey responses, addressing issues of construct validity and reliability. The results highlight twenty-six F&R in the set of the three suggested typologies of project management offices: seven for the basic, ten for the intermediate, and nine for the advanced project management office.